2020
DOI: 10.5530/jyp.2020.12s.47
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Levodopa Loaded Pharmacosomes for Brain Targeting via Intranasal Route: Pharmacodynamic Evaluation in Rats

Abstract: Original Article optimized formulation (F7), drug solution via nasal route was compared with drug solution administered orally, in rotenone induced male wistar rats. Group treated with optimized pharmacosomes formulation (F7) showed significant recovery in rat weight (43%), locomotor activity by photo actometer (90%) and grip strength on retard (65%) compared to drug solution treated orally showed recovery in rat weight (32%), locomotor activity by photo actometer (57%) and grip strength on rotarod(30%). Bioch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The study further demonstrated more pronounced yields by the chlorotoxin-tagged liposomes suggesting target-specific effects . Treatment with L-DOPA-loaded pharmacosomes was found to attenuate motor deficits and reduce oxidative stress and neuron damage in the substantia nigra region of the brain of PD rats in a significantly pronounced manner than exhibited by free L-DOPA …”
Section: Advances Made In Pd Treatment Strategies With the Assistance...mentioning
confidence: 99%
See 1 more Smart Citation
“…The study further demonstrated more pronounced yields by the chlorotoxin-tagged liposomes suggesting target-specific effects . Treatment with L-DOPA-loaded pharmacosomes was found to attenuate motor deficits and reduce oxidative stress and neuron damage in the substantia nigra region of the brain of PD rats in a significantly pronounced manner than exhibited by free L-DOPA …”
Section: Advances Made In Pd Treatment Strategies With the Assistance...mentioning
confidence: 99%
“…154 Treatment with L-DOPAloaded pharmacosomes was found to attenuate motor deficits and reduce oxidative stress and neuron damage in the substantia nigra region of the brain of PD rats in a significantly pronounced manner than exhibited by free L-DOPA. 163 Another approach to PD treatment includes the administration of dopamine; however, exogenous dopamine has a poor BBB permeability, and thus an efficient carrier strategy might prove fruitful in increasing the bioavailability of dopamine in the brain. 148 Treatment with dopamine-loaded liposomes was found to exhibit sustained release of the loaded drug, restore motor functions, and increase striatal dopamine levels in a PD rat model.…”
Section: Nanovesicle-aided Delivery Of Drugs Targeting Dopamine Deple...mentioning
confidence: 99%
“…Targeting anti-tumor therapy [175] Ibuprofen and Phosphatidylcholine from soy Anti-inflammatory [176] Levodopa, egg lecithin and chitosan Parkison's treatment [177] Naproxen and soy lecithin Rheumatoid arthritis treatment [178] Rosuvastatin, soy lecithin and cholesterol Hyperlipidemia treatment [179]…”
Section: Pharmacosomesmentioning
confidence: 99%